Conditional Inactivation of Blimp1 in Adult Mice Promotes Increased Bone Mass - Miyauchi, Yoshiteru (American Society for Biochemistry and Molecular Biology, 2012)
Bone resorption, which is regulated by osteoclasts, is excessively activated in bone destructive diseases such as osteoporosis. Thus, controlling osteoclasts would be an effective strategy to prevent pathological bone loss. Although several transcription factors that regulate osteoclast differentiation and function could serve as molecular targets to inhibit osteoclast formation, those factors have not yet been characterized using a loss of function approach in adults. Here we report such a study showing that inactivation of B-lymphocyte induced maturation protein 1 (Blimp1) in adult mice increases bone mass by suppressing osteoclast formation. Using an ex vivo assay, we show that osteoclast differentiation is significantly inhibited by Blimp1 inactivation at an early stage of osteoclastogenesis. Conditional inactivation of Blimp1 inhibited osteoclast formation and increased bone mass in both male and female adult mice. Bone resorption parameters were significantly reduced by Blimp1 inactivation in vivo. Blimp1 reportedly regulates immune cell differentiation and function, but we detected no immune cell failure following Blimp1 inactivation. These data suggest that Blimp1 is a potential target to promote increased bone mass and prevent osteoclastogenesis.